Case report: Post-surgical complication in a case of urethral duplication in a dog - Martins, Joana B.; Rosa, Rita; Iglésias, Leonor V.; Reisinho, Ana; Mestrinho, Lisa A. (Frontiers in Veterinary Science, 2022)
Urethral duplication is a rare anomaly observed in veterinary medicine. The surgical techniques described therein are associated with an uneventful recovery. The authors describe a major surgical complication after the correction of urethral duplication in a two-year-old male Yorkshire terrier. After surgical correction using the perineal approach, the patient developed pollakiuria and urinary retention due to a valve effect caused by the remnant of the dorsal opening of the ectopic urethra. A second procedure, using an abdominopelvic approach, successfully corrected the complication by intraluminal correction of the dorsal urethral wall.